SOSIALISASI BAHAYA HIDROQUINON PADA CREAM PENCERAH WAJAH MELALUI PENYULUHAN KESEHATAN DI KEL. TAMARUNANG KEC. SOMBAOPU KAB. GOWA - wati, Rahma; Arisanti, Dewi; Fatmawati, Andi; Hasnah, Hasnah (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2024)
Cosmetics are an element that has a very important role in human life, where some people are very dependent on cosmetic preparations for every occasion. The use of chemicals in cosmetics can endanger health. A survey of the community in Tamarunang Village, Sombaopu District, Gowa Regency, found that there were still mothers and teenagers who bought and used domestically produced and imported cosmetic products without distribution permits containing hydroquinone. Therefore, community service efforts are being made so that people can protect themselves against dangerous cosmetic products. This activity was carried out using the method of increasing the knowledge of 35 participants with an age range of 25 to 55 years. This service activity aims to increase knowledge, especially for the people of Tamarunang Village, Sombaopu District, Gowa Regency. about cosmetics that are safe, free of chemicals and dangerous ingredients and how to use them correctly. Select it. After participating in this service activity, it was discovered that the level of knowledge of the participants was at a fairly high level, namely 85.6%.